2018
DOI: 10.1016/j.matchemphys.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Nano-objects synthesized from Cu, Ag and Cu28Ag72 electrodes by submerged discharges in liquid nitrogen

Abstract: Discharges in liquid nitrogen between 2 electrodes made of either Cu, Ag or Cu28Ag72 enable the production of several types of comparable nano-objects. First, Cu nanoparticles (NPs) with sizes close to 5±4 nm nm and 40±10 nm are obtained with Cu electrodes and get oxidized in the air to form CuO after liquid evaporation. With Cu28Ag72 electrodes, copper contains a small amount of silver that inhibits oxidation. Next, silver nanoparticles are spherical but when doped with copper, they are facetted. Silver-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Alloyed NPs are already observed after the sole plasma treatment unlike what had been reported for a pin-topin configuration, with electrodes made of pure Cu and Ag [41]. This shows some difference in the physical processes at stake when using powders rather than bulk electrode as the initial source material.…”
Section: Characterization Of Npsmentioning
confidence: 65%
“…Alloyed NPs are already observed after the sole plasma treatment unlike what had been reported for a pin-topin configuration, with electrodes made of pure Cu and Ag [41]. This shows some difference in the physical processes at stake when using powders rather than bulk electrode as the initial source material.…”
Section: Characterization Of Npsmentioning
confidence: 65%
“…Irregular round-shaped particles were synthesized mainly in Ti 5 A, while most cubic morphology particles were observed in Ti 30 A. The cubic-shaped particle was reported as the crystal structure of TiN [ 39 , 40 , 41 ]. To confirm the component of cubic particles, EDS elemental mapping was conducted during the FE-SEM observation.…”
Section: Resultsmentioning
confidence: 99%
“…As a product, they also obtained Al, Ti, V, Fe, Ni, Cu, Zr, Nb, Mo, Ta, and W micro-size particles using a DC power supply [ 36 ]. Belmonte et al also reported synthesizing Cu, Ag, Pb, CoNi, and ZnO nanoparticles using a nano-pulse power supply [ 30 , 37 , 38 , 39 , 40 , 41 , 42 ]. Sano et al presented the synthesis of Pt-supported carbon nanohorns for fuel cell electrodes [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Processes based on discharges in liquids are commonly used to synthesize original nanoobjects with high yields [ 1 , 2 , 3 , 4 , 5 ]. In liquid nitrogen, they are particularly interesting, as they lead to the synthesis of two-dimensional structural materials like nanosheets [ 6 , 7 , 8 ], exhibiting high levels of selectively exposed reactive facets and the fast separation of electrons and holes.…”
Section: Introductionmentioning
confidence: 99%